Fibrillar assembly of whey protein isolate and gum Arabic as iron carrier for food fortification. (July 2022) - Yue, Jianxiong; Shu, Meng; Yao, Xiaolin; Chen, Xiaoyu; Li, Dan; Yang, Dan; Liu, Ning; Nishinari, Katsuyoshi; Jiang, Fatang
Abstract: In this study, fibrous aggregates of whey protein isolate (WPI) and gum arabic (GA) containing ferric ions were fabricated, and its fibrillation process, morphology, secondary structure, driving force, iron release in simulated gastrointestinal phase as well as its sensory properties have been investigated. The results indicated that WPI/GAFe3+ fibrils could be well formed at the mass ratio of 15: 1, concentration of 2.0 wt%, pH 3.0, heated at 90 °C for 5 h. It was observed by scanning electron microscopy and found that the nanospheric GAFe3+ was regularly entangled at the end or junction of WPI fibrils. Both circular dichroism and FTIR confirmed that secondary conformations of protein have been transformed into specific forms during the fibrilization, along with an increase of β-sheet and a decrease of α-helix. The addition of SDS disintegrating the WPI/GAFe3+ fibrils revealed the significant contribution of intermolecular hydrophobic interaction as the dominant driving forces for the formation of WPI/GAFe3+ fibrils. The iron ions release showed a significant delay in the gastric phase and followed by a rapid increase in the intestinal phase, profitable for the orally administered products with high absorption in duodenum. Moreover, the WPI/GAFe3+ fibrils exhibited higher sensory scores compared with WPI/GAFe3+ nanoparticles on the attributes of texture, color, odor and acceptance. Thus, the proposed fabrication of WPI/GAFe3+ fibrils complexes is expected to be promising for iron fortification in food industry. Graphical abstract: Image 1 Highlights: Fibrillar assembly of WPI and GAFe3+ was an enhanced fabrication for the iron fortification. β-sheet and antiparallel β-sheet increased and α-helix decreased during protein fibrillation. Intermolecular hydrophobic interaction was the dominant driving forces for WPI/GAFe3+ fibrils formation.